LBP-1.08 Preliminary report on experience with point of care syphilis and HIV testing in hard-to-reach populations in outreach settings in Edmonton, Canada. (10th July 2011) - Bergman, J; Plitt, S; Gratrix, J; Conroy, P; Li, J; Rocco, K; Fenton, J; Archibald, C; Wong, T; Singh, A
Abstract : Background: Edmonton is in the midst of a syphilis outbreak occurring largely in high risk and hard-to-reach populations. Point of care (POC) testing for syphilis and HIV offers the opportunity for immediate and rapid access to testing, and in the case of syphilis, immediate treatment. POC syphilis tests have not been previously evaluated in clinical settings in Canada. Methods: Since 14 February 2011, treponemal syphilis (Bioline Syphilis 3.0) and HIV (INSTI HIV-1/HIV-2 Antibody Test) POC testing, using whole blood from a finger prick specimen, has been offered to outreach clients in Edmonton. POC results were compared to standard testing from simultaneously collected serum specimens. Baseline demographics, sexual and drug use risk behaviour information were collected. Age and gender were collected on individuals who refused POC testing. A descriptive analysis was performed on the characteristics and outcomes of participants and those who refused. Results: As of 15 April 2011, 146 individuals had been offered POC testing; 85.6% (n=125) consented. Among participants, 59.2% (74) were male [vs 66.7% (14) of non-participants, p=0.5)] and the median age was 29 yrs (IQR 24–36 yrs) [vs non-participants median age 29 yrs (IQR 25–45 yrs), p=0.2)]. The majority of participants (83.2%; 104) were heterosexual, 59.2% (69) were Aboriginal, and 30.4% (38) reported injection drug use. Among females, 62.7% (32) reported sex trade involvement, while among males, 21.6% (16) reported sex with a sex trade worker. Of 121 syphilis treponemal POC tests, 5 (4.1%) were positive, all in old treated cases of syphilis that were asymptomatic for infectious syphilis at the time of testing. Two syphilis POC (1.7%) tests were falsely negative when compared to the standard screening test (Architect Syphilis TP Microparticles, Abbott Laboratories, Illinois, USA); both were in individuals previously treated for syphilis. Of 123 HIV POC tests, 2 (1.6%) were reactive, both newly diagnosed cases as confirmed by GS HIV-1 Western Blot (BioRad Laboratories, California, USA); both were negative by syphilis POC tests. Conclusion: Preliminary results from Edmonton suggest that POC testing for syphilis and HIV is well accepted among high-risk populations in outreach settings in Edmonton. This ongoing study will assess the utility of these tests in mitigating the further spread of both syphilis and HIV through POC testing, and in the case of syphilis, POC treatment.